2018
DOI: 10.1111/disa.12323
|View full text |Cite
|
Sign up to set email alerts
|

Disaster studies inside out

Abstract: Disaster studies is faced with a fascinating anomaly: frequently it claims to be critical and innovative, as suggested by the so‐called vulnerability paradigm that emerged more than 40 years ago, yet often it is perpetuating some of the core and problematic tenets of the hazard paradigm that we were asked to challenge initially. This paper interrogates why such an anomaly persists. In so doing, it employs Antonio Gramsci's concept of hegemony to unpack why disaster studies is still dominated by Western epistem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 20 publications
(32 reference statements)
0
112
0
9
Order By: Relevance
“…In addition to being important on an individual and communal level (Fiddian-Qasmiyeh, 2014a; Gaillard et al, 2017), this also includes addressing the structural factors and processes that prevent lives from being lost, when knowledge and mechanisms clearly exist to do so. A recurrent theme at the fortieth anniversary conference of Disasters was how to implement what we already know, rather than continuing to find new avenues for research and practice that ultimately often end up 'recycling' longstanding proposals (Gaillard, 2018). Indeed, one key challenge, in the context of current and future disasters, is how to put into practice what we have collectively come to know, when resources either are not provided or are implicitly or explicitly blocked, and when responsibilities are shunned or dodged rather than upheld.…”
Section: Mass Experiences and Intersectionalitymentioning
confidence: 99%
“…In addition to being important on an individual and communal level (Fiddian-Qasmiyeh, 2014a; Gaillard et al, 2017), this also includes addressing the structural factors and processes that prevent lives from being lost, when knowledge and mechanisms clearly exist to do so. A recurrent theme at the fortieth anniversary conference of Disasters was how to implement what we already know, rather than continuing to find new avenues for research and practice that ultimately often end up 'recycling' longstanding proposals (Gaillard, 2018). Indeed, one key challenge, in the context of current and future disasters, is how to put into practice what we have collectively come to know, when resources either are not provided or are implicitly or explicitly blocked, and when responsibilities are shunned or dodged rather than upheld.…”
Section: Mass Experiences and Intersectionalitymentioning
confidence: 99%
“…Peters et al (2019b) suggested that cavalier DRR activities have the potential to escalate conflict in certain circumstances. Ker-Lindsay (2007) noted that conflicts tend to be multidimensional, stemming from multiple factors, and they are dynamic as parties take various actions or inactions and as new issues emerge-a summary and ethos that matches the findings from decades of disaster research (Gaillard 2019). When viewed through a disaster diplomacy lens, ''conflict and non-conflict disasters are inextricably linked'' (Kelman 2012, p. 1), since both types of disasters are constructed through patterns of human action and inaction and emerge from this history.…”
Section: Pivoting Toward Peace With Disaster Diplomacymentioning
confidence: 99%
“…In this section, we will provide a brief overview of the meanings of and debates around the terms that we are discussing in this paper (the summary is presented in Table 1). We will also demonstrate some of the translations to emphasise that the terms used in disaster studies are not only conceptualised in English but are also tied to a particularly Anglophone approach to research (Kelman, 2018;Gaillard, 2019).…”
Section: Terminologymentioning
confidence: 99%